Iberverin exhibits antineoplastic activities against human hepatocellular carcinoma via DNA damage-mediated cell cycle arrest and mitochondrial-related apoptosis - Zhang, Yuting; Du, Jiao; Jin, Libo; Pan, Liying; Yan, Xiufeng; Lin, Sue (Frontiers in Pharmacology, 2023)
Hepatocellular carcinoma (HCC) is one of the malignant tumors with high incidence and mortality rates in the world. Isothiocyanates (ITCs), bioactive substances present primarily in the plant order Brassicales, has been proved to be promising candidates for novel anti-HCC drugs with chemopreventive and anticancer activities. Iberverin, a predominant ITC isolated from the seeds of oxheart cabbage, has been discovered with anticancer property in lung cancer cells. However, the roles of iberverin in HCC remain elusive. In the present study, the effect and potential mechanisms of iberverin against human HCC were dissected. We demonstrated that low concentrations of iberverin inhibited cell proliferation, suppressed migration and induced mitochondrial-related apoptosis in vitro, and hampered tumorigenicity in vivo, with no obvious toxicity. Furthermore, we found that iberverin treatment induced DNA damage and G2/M phase arrest. Iberverin treatment also caused increased intracellular reactive oxygen species formation and glutathione depletion. Taken together, these results suggest that iberverin promotes mitochondrial-mediated apoptosis and induces DNA damage and G2/M cell cycle arrest in HCC by enhancing oxidative stress. Our findings provide better understanding of the anti-HCC mechanisms of ITCs and the potential for the natural product iberverin as a promising new anti-HCC biotherapeutic.